Unidirectional emission in an all-dielectric nanoantenna. (27th February 2018) - Feng, Tianhua; Zhang, Wei; Liang, Zixian; Xu, Yi
Abstract: All-dielectric nanoantennas are a promising alternative to plasmonic optical antennas for engineering light emission because of their low-loss nature in the optical spectrum. Nevertheless, it is still challenging to manipulate directional light emission with subwavelength all-dielectric nanoantennas. Here, we propose and numerically demonstrate that a hollow silicon nanodisk can serve as a versatile antenna for directing and enhancing the emission from either an electric or magnetic dipole emitter. When primarily coupled to both electric and magnetic dipole modes of a nanoantenna, broadband nearly-unidirectional emission can be realized by the interference of two modes, which can be spectrally tuned via the geometric parameters in an easy way. More importantly, the emission directions for the magnetic and electric dipole emitters are shown as opposite to each other through control of the phase difference between the induced magnetic and electric dipole modes of the antenna. Meanwhile, the Purcell factors can be enhanced by more than one order of magnitude and high quantum efficiencies can be maintained at the visible spectrum for both kinds of dipole emitters. We further show that these unidirectional emission phenomena can withstand small disorder effects of in-plane dipole orientation and location. Our study provides a simple yet versatile platform that can shape the emission of both magnetic and electric dipole emitters.